TA’LIM SALAM AL ISLAMY KHILAL AL MADDAH AL ARABIYAH LIL AGHRADH AL KHOSHOH FI MAJAL AL IQTISHODIY LIL MARHALAH AL JAMI’IYAH - Desmadi Saharuddin; Meirison Meirison; Nuril Mufidah (Universitas Islam Raden Rahmat Malang, 2018)
This study aims to prepare the Arabic study material for special purposes in the field of economics for the undergraduate stage. This is because of the lack of a source and the proper book in this area in Indonesia. The researchers presented a particular paper in the economic field of the university model. With regard to necessary of terrorism in the country of Indonesia, this book shows this presentation, the financial aspects of the phenomenon of terrorism, through the relationship of terrorism to the economy, and the definition of economic reasons leading to it, and clarify the economic implications and the mechanisms to discuss it from the perspective of the IslÄmic economy. Of terrorism causes, and economic justifications which often cause an imbalance in the state budget and confusion in financial and investment transactions and occur underdevelopment